Highly Specific Chemiluminescence Immunoassay for the Determination of Chloramphenicol in Cosmetics - Qiyan Li; Riran Zhu; Jun Li; Xiaobing Wang; Lihua Xu; Yanshen Li; Peng Li (International Journal of Analytical Chemistry)
A direct and highly specific chemiluminescent enzyme-linked immunosorbent assay (CL-ELISA) method for monitoring chloramphenicol (CAP) in cosmetics has been developed. The anti-chloramphenicol antibody (mAb) adopted in this work for direct immunoassay could bind to CAP specifically, with negligible cross-reactivity (CR) (less than 0.01%) with most CAP analogues, including structurally related thiamphenicol (TAP) and florfenicol (FF). The limit of detection (LOD), measured by IC10, was 0.0021 ng mL−1. The detection range (IC20-IC80) was ranged from 0.00979 to 0.12026 ng mL−1. In spiked cosmetics samples, mean recoveries ranged from 82.7% to 99.6%, with intraday and interday variation less than 9.8 and 8.2%, respectively. Moreover, with the help of HRP-labeled anti-CAP mAb, the method could be processed in fast direct immunoreaction mode. This CL-ELISA method could be applied for specific, rapid, semiquantitative, and quantitative detection of CAP in cosmetics, facilitating the precise quality control of CAP contamination.